2023
DOI: 10.3390/cells12030346
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Treatment with Rho-Associated Kinase Inhibitor Preserves Keratinocyte Stem Cell Characteristics In Vitro

Abstract: Primary keratinocytes including keratinocyte stem cells (KSCs) can be cultured as epidermal sheets in vitro and are attractive for cell and gene therapies for genetic skin disorders. However, the initial slow growth of freshly isolated keratinocytes hinders clinical applications. Rho-associated kinase inhibitor (ROCKi) has been used to overcome this obstacle, but its influence on the characteristics of KSC and its safety for clinical application remains unknown. In this study, primary keratinocytes were treate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…On the keratinocyte dataset [9], we again found that Dawnn and CNA identified a larger proportion of DA regions than Milo and DA-seq (Figure 3b). Dawnn had higher TPRs than CNA for larger simulated log-fold changes.…”
Section: Growth-accelerated Keratinocytesmentioning
confidence: 61%
See 1 more Smart Citation
“…On the keratinocyte dataset [9], we again found that Dawnn and CNA identified a larger proportion of DA regions than Milo and DA-seq (Figure 3b). Dawnn had higher TPRs than CNA for larger simulated log-fold changes.…”
Section: Growth-accelerated Keratinocytesmentioning
confidence: 61%
“…We follow the benchmarking of Dann et al (Section 4.2.2), creating simulated and real datasets using their described approach [1]. We further assessed real-world performance using three additional biological datasets: one from a publication of ours examining the effects of accelerating skin sheet growth [9]; another from a publication characterising organoids of bile ducts [10]; and a large dataset comprising cells from the heart in a study of congenital heart disease [11]. Table 1 summarises our benchmarking datasets.…”
Section: Dawnn Detects Differentially Abundant Regions With Higher Ac...mentioning
confidence: 99%
“…However, it is important to note that Jayarajan et al, used de‐epidermalized dermis as a base for generating such matured cultures in vitro. [ 11 ] Rather, the main focus of this study was to elucidate the compatibility and feasibility of bio‐electrospraying human primary fibroblasts in combination with a collagen hydrogel and subsequently keratinocytes in complete media, but not on de‐epidermalized dermis.…”
Section: Resultsmentioning
confidence: 99%
“…HKs were cultured as previously described. [ [ 11 Briefly, HKs were cultivated in a humidified atmosphere at 37 °C with 10% CO 2 in Green's medium containing DMEM and DMEM/F12 in the ratio of 1:1 supplemented with 10% FCS (Labtech, Heathfield, UK, # FCS‐SA), 50 U mL −1 penicillin and streptomycin (Gibco, Paisley, UK, # 15 070 063), 10 ng mL −1 EGF (Peprotech, London, UK, # AF‐100‐15‐1000), 0.4 µg mL −1 Hydrocortisone (Sigma, Gillingham, UK, # H‐2270), 5 µg mL −1 Transferrin (Sigma, # T2252), 5 µg mL −1 Insulin (Sigma, # I‐5500), 2 × 10 −11 m Liothyronine sodium salt (Sigma, # T6397), and 1 × 10 −10 m Cholera toxin (Sigma, # C‐8052). keratinocytes were passaged and reseeded at a density of 1.5 × 10 4 cm −2 .…”
Section: Methodsmentioning
confidence: 99%
“…For each location, references to the papers that performed the biopsies are listed in chronological order. (A) Foreskin [31][32][33]; (B) Scalp [31,34,35]; (C) Body trunk [25,31,34,36]; (D) foot [37,38]; (E) hip [38]; (F) hand [34,38]; (G) inguinal region [37,39]; (H) leg [40]; (I) buttocks [41,42]; (J) arm [30,34,40]; (K) face (forehead, eyelid, and tragus) [34,[43][44][45]; (L) neck [43]. to be analyzed with single-cell techniques.…”
Section: Skin Biopsy Processingmentioning
confidence: 99%